Metode Taguchi Sebagai Salah Satu Alternatif Pengendalian Biaya Mutu - Barbara Gunawan (Universitas Muhammadiyah Yogyakarta, Indonesia, 2001)
The requirement for the company to compete and exist in the global market is to produce quality products in accordance with established standards. If the product is not qualified to consumers it would appear that the claim is a sign of the emergence of quality cost. One of the current quality control methods used in the United States is the Taguchi method developed by Genichi Taguchi, which uses statistical methods ekuipment design to enhance product design. The strategy used is to create quality products and against disturbances by eliminating the impact caused by the interference and eliminate the causes of the disorder. Interference in question can be a bad product, the production is not perfect, and environmental factors. Taguchi method is intended to measure the impact of quality on the costs by centralizing production consists of three stages of system design, parameter design and tolerance design.